Re-Aligning the Dalit Feminist Prospective in 21st Century India - Kashyap, Dr. Tanu (International Journal of Psychosocial Rehabilitation, 2020)
Literature is the mirror of society without any boundary of language. It successfully portrays the on- going turmoil within the society- subtle or overt. The major stakeholder in the Indian society is the second gender as they constitute half of the Indian demography. Our scriptures have given the place of goddess to women but the reality check is totally opposite to the popular assumptions. The term “woman” portrays a picture of oppressed second gender, is not always given due recognition in society. Her portrayal has been more akin to a second citizen of this country. As Indian societal segregation has four major Varnas, the plight of a Dalit woman is beyond doubt even more painful. Strangely enough the Indian literature in English was very vocal about the Feminist issues but the plight of Dalit woman was not adequately acknowledged. However the Dalit women were made a part of romantic narratives, which were far from the reality of caste bifurcation. The era of 1980 saw a sudden upsurge of women Dalit writers who were perturbed with the fact that the feminist perception was covering upper and middle class women only. There was no representation of the underprivileged Dalit women; writers like Shantabai Kamble, Urmila Panwar, Babytai Kamble, Kumud Pawade, Gogu Shyamala, Vijila Chirrappad have highlighted the oppression of the second gender in their respective mother tongue.This research paper will analyse the fiction of two most prominent women novelists who have enriched their respective vernacular literature. Both the women novelists have tried to bring forth the plight of women who are marginalized both more importantly about Dalit women who are doubly marginalized. Volga is a non-Dalit Telugu poet and writer well known for her feminist perspective whereas Palanimuthu Sivaakmi is an Indian Dalit Feminist writer who writes in Tamil. The interesting fact is that they have written about women - both are from South India- both bring about the double whammy faced by Dalit women. But there are dissimilarities in terms of their treatment of their feminist perspectives, and they have discussed the socio- political, social-economic disparities which are prevalent in the Indian society at large.